Janko Polić-Kamov - Precursor of the Croatian Avant-Garde - Gjurgjan, Ljiljana Ina (Array, 1997)
The article shows how the work of Janko Polić-Kamov chronologically belongs to Croatian turn-of-the-century literature, but aesthetically differs from it despite the similarity of motifs. Kamov's aesthetics will usher in the avant-garde, and the existential themes of the later period.